Requiring Disclosure of the Origin of Genetic Resources and Prior Informed Consent in Patent Applications Without Infringing the TRIPS Agreement: The Problem and the Solution - Nuno Pires de Carvalho (Washington University Journal of Law & Policy, 2000)
The purpose of this Article is to discuss how the requirement that the origin of genetic resources and prior informed consent be disclosed in patent applications can be adopted by World Trade Organization Members at the national, regional, or international levels without infringing the TRIPS Agreement.
Keywords: Discovery (Law); Genetic engineering; Patents (International law); Agreement on Trade-Related Aspects of Intellectual Property Rights